Neuroprotective effects of silk fibroin hydrolysate against Aβ25–35 induced cytotoxicity in SH-SY5Y cells and primary hippocampal neurons by regulating ROS inactivation of PP2A. (June 2018) - Xu, Zheng; Chen, Song; Wang, Ying; Chen, Suting; Yao, Wenbing; Gao, Xiangdong
Highlights: SFH had neuroprotective effect in cultured cells. SFH reduced Aβ-induced ROS in cultured cells. SFH inhibited PP2A phosphorylation by suppressing Aβ-induced ROS. SFH protected cells from Aβ-induced injury via PP2A/MAPKs and PP2A/tau pathway. Abstract: Silk fibroin (SF) has been widely used as biomedical materials and the hydrolysate form of SF (SFH) has shown many activities. The purpose of the current study was to explore the neuroprotective effects of SFH against Aβ25–35 -induced cytotoxicity in SH-SY5Y cells and primary hippocampal neurons and the possible mechanism. The results showed that SFH could improve the viabilities of SH-SY5Y and primary hippocampal neurons injured by Aβ25–35 . The lowered mitochondrial membrane potential and increased cell apoptosis induced by Aβ25–35 were recovered after SFH treatment. Further study indicated that the beneficial effects of SFH were likely due to its interference with reactive oxygen species (ROS). SFH inhibited the phosphorylation of Ser/Thr protein phosphatase 2A (PP2A) by suppressing Aβ25–35 -induced ROS, and then suppressed the activation of MAPKs and tau hyperphosphorylation, and protected SH-SY5Y cells and primary neurons from Aβ25–35 -induced damages. SFH has the potential to be a nutraceutical for AD intervention.